WAQF AS AN INSTRUMENT FOR YOUTH EMPOWERMENT TO ATTAIN THE HIGH LEVEL OF HUMAN CAPITAL FOR PEACEFUL COEXISTENCE IN KANO - Gwadabe Nura Abubakar; Asmak Ab Rahman (Journal of Islamic, Social, Economics and Development, 2021)
The Study was aimed in examining the Potentials of Waqf for youth empowermentfor attaining high level of Human capital among the Youth for peaceful coexistence in Kanostate Nigeria. Human Capital signifies the Knowledge, attitude, expertise and skills possess byHuman being, It is believe that Human capital is the most significant factor among the factorsof production, it direct the other factors of production in the provision of good and services tothe nation towards the attainment of social and economic development. Awqaf institutions haveplayed a vital role to the development of Human capital in various Muslim Communities morespecifically through Education, Hygiene and Health Care Services. The Studies has shown thatNigeria was ranked the 11th in the world among the countries that has the highest labor force,and most of these youth are either unemployed or unemployable. These youth can be easilyrecruited into thuggery, political violence and other social vices that will disturb the peace andpeaceful coexistence of the state. To ensure peace and security in Kano, utmost priority mustbe given to Youth Empowerment in the areas of Education, training, skills and abilities of theyouth. The study adopted the qualitative method of research, whereas, relevant documents wereconsulted as structured interview was designed to ascertain the role of waqf based youthempowerment programs in achieving high level of human capital in Kano. The data wereanalyzed using thematic data analysis. The study concluded that Awqaf institutions in Kanohas played a vital role in the Youth empowerment for the actualization of High level of Humancapital in Kano towards the attainment of peaceful society.